Teachers’ leadership during the pandemic: balancing between students and professional needs - Juharni , Indra; Suyatno, Suyatno; Sugiarti, Sugiarti; Uswah , Uswah (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The Covid-19 pandemic caused learning loss for students at almost all educational levels, including elementary schools. Teachers’ leadership is important in solving the various problems students face in learning during the pandemic. This study aimed to explore teachers’ leadership in improving learning quality in elementary schools during the pandemic. The data collected using semi-structured interviews with ten teachers of elementary schools in Yogyakarta were analyzed through thematic analysis. The analysis showed two significant themes of teachers’ leadership in improving learning quality during the pandemic in elementary schools. The two themes are to realize students’ needs and professional development. The theme on realizing students’ needs is formed by two sub-themes of convenience learning for students and serving their individual needs. Moreover, the theme for professional development is formed by four sub-themes. These move the organization, utilizing digital platforms, colleague collaboration, and innovation. The results showed that the implementation of teachers’ leadership in elementary schools during the pandemic was oriented to students and professional needs. Therefore, teachers need to balance students and professional needs to improve learning quality.